Сварной комбинированный ротор паровой турбины К-325-23,5 - Гришин, Николай Николаевич; Зайцев, Борис Филиппович; Пальков, Игорь Андреевич; Кантор, Александр Геннадиевич; Пащенко, Юрий Григорьевич (Национальный технический университет "Харьковский политехнический институт", 2019)
Представлены результаты разработки сварного комбинированного ротора среднего давления паровой турбины нового поколения К-325-23,5 производства АО "Турбоатом". При разработке использовались результаты опытно-конструкторских и научно-исследовательских работ по выбору рациональных форм отдельных дисков и мест расположения кольцевых перемычек со сварными швами для обеспечения приемлемого уровня напряжений, что является одним из основных требований при проектировании сварных роторов.

The development data of the welded combined average-pressure rotor for the steam turbine of a new generation К-325-23.5 produced by JSC "Turboatom" have been given. To develop it, we used the data given in experimental-&-engineering and research papers devoted to the selection of the rational forms of individual discs and the loci of circular cofferdams with welded seams to provide an acceptable level of stresses, which is one of the main requirements to be met when designing welded rotors. The mode of deformation of some options of a new rotor structure was defined using the method of finite elements and the software of IPMach of the National Academy of Sciences of Ukraine. In addition to the stresses that arise under the action of centrifugal forces and thermal stresses we took into account during our computations low bending alternating stresses caused by weight loads and these stresses are very dangerous due to their cyclic character. When combined with tensile stresses caused by centrifugal forces at the bottom run of welded seams, these can result in an increased amount of possible defects. The experimental-&-engineering research done by us allowed for the transformation of aggravating stresses caused by centrifugal forces at the bottom run of welded seams into compressive stresses. A special research was done to select the weld groove geometry, electrodes, the weld technology and thermal treatment modes after the welding to remove residual stresses. Welded specimens with the welded seams of a different configuration (type of weld groove geometry) and the specimens cut out of the welded seams of the end parts of fullscale model were subjected to fatigue tests. A high workability and unavailability of drawbacks that are peculiar for the rotors with capped discs individualize this type of rotor advantageously in comparison with the latter. Expensive balancing work requires the reduction of start operations by a factor of two. A combined "composite" rotor behaves in a more consistent manner with the spin up during the transition across critical rotation frequencies and at rated revolutions; a smoother operation is observed.
Welded combined rotor for the steam turbine K-325-23.5
Keywords: насадной диск; вал; температура пара; эквивалентные напряжения; твердость сварного соединения; capped disk; shaft; steam temperature; equivalent stresses; welded junction hardness